2016
DOI: 10.1302/0301-620x.98b1.35832
|View full text |Cite
|
Sign up to set email alerts
|

Is removal of the implants needed after fixation of burst fractures of the thoracolumbar and lumbar spine without fusion?

Abstract: Implant removal may not be needed for patients with burst fractures of the thoracolumbar and lumbar spine after fixation without fusion. However, information should be provided beforehand regarding the possibility of screw breakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…This result is especially relevant because kyphosis after implant removal and whether implants should be removed have recently been topics of discussion in the literature. [ 11 , 12 , 23 , 24 ] For example, Jeon et al [ 23 ] reported improvement in functional outcomes after implant removal in patients who underwent long-segment fixation using the fusion technique. In contrast, Chou et al [ 24 ] found no changes in radiological and functional outcomes after implant removal in patients treated with short-segment fixation.…”
Section: Discussionmentioning
confidence: 99%
“…This result is especially relevant because kyphosis after implant removal and whether implants should be removed have recently been topics of discussion in the literature. [ 11 , 12 , 23 , 24 ] For example, Jeon et al [ 23 ] reported improvement in functional outcomes after implant removal in patients who underwent long-segment fixation using the fusion technique. In contrast, Chou et al [ 24 ] found no changes in radiological and functional outcomes after implant removal in patients treated with short-segment fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of motion of the surgical segment leads to high stress on the fixation implant, increasing mobility, and intradiscal pressure at adjacent levels 3 . This may result in adjacent segment degeneration and loosening/rupture of the fixation implant [4][5][6][7][8][9] . Non-fusion and dynamic fusion instruments have been designed to prevent adjacent segment disease.…”
Section: Introductionmentioning
confidence: 99%
“…24 In our review, implant removals that resulted from system failure were evaluated. 4,21 The odds ratio for removal of a fixation system was 4.09 higher in the no-fusion group than in the fusion group; however, a sensitivity analysis in a study by Chou et al 5 found a high relative weight. The evaluation of this variable was also limited because part of the system removal described in the trials was found to be related to cultural factors and not failure only.…”
Section: Discussionmentioning
confidence: 99%